White Saviour Complex and (Mis)Portrayal of Blacks in Kathryn Stockett’s The Help - Sarah Abdullah, Alesha Nasir (Journal of Research in Humanities, 2023)
This article critiques the use of the white saviour trope in American fiction. Taking Kathryn Stockett’s debut novel The Help (2009) under study, the article argues that the text’s black female characters’ assertions of power and agency are subverted by their characterization as faithful mammies and maids who need the white female protagonist to exercise their agency and emancipate themselves. Instead of destabilizing the binary between blacks and whites, Stockett reaffirms them by positioning a white female character, Skeeter, as its central narrator. Hence, Stockett’s attempt to critique the imperialist nature of white society ends up in recapitulating the message that only a white person can rescue blacks from a life of drudgery. In a broader context, the article problematizes the use of a white saviour as a subversive trope as it does little to dismantle the institutional, ideological and systematic racism that primarily privileges whites over blacks.